Neonatal adrenal insufficiency - beyond the common causes - Inês Pires Duro; Sara Mosca; Graça Araújo; Joana Lorenzo; Catarina Figueiredo; Joana Freitas; Maria João Oliveira; Teresa Borges (Hygeia Press di Corridori Marinella, 2021)
Background: Primary adrenal insufficiency (PAI) can be caused by multiple etiologies. One of the rarest is X-linked adrenal hypoplasia congenita (AHC), a disorder of adrenal development that results from mutations in the NR0B1/DAX1 gene and in which half of the affected males present with salt loss and glucocorticoid insufficiency at birth or in early infancy. In adolescence, hypogonadotropic hypogonadism with absent or arrested pubertal development occurs. Pharmacological intervention is mandatory. Case presentation/discussion: We report 2 male brothers that presented in early infancy with a salt-wasting crisis. Congenital adrenal hyperplasia (CAH) was the presumptive diagnosis, and treatment was instituted accordingly. However, 17-hydroxyprogesterone levels were normal, requiring the search for alternative causes of adrenal insufficiency. In case 2, treatment was discontinued, and he lost follow-up, but he remained well. When he was evaluated due to generalized skin hyperpigmentation, the association of PAI in 2 male brothers raised the suspicion of X-linked AHC and allowed the definitive diagnosis. Conclusions: These 2 cases highlight the importance of a high index of suspicion when facing a male newborn with PAI in which CAH was excluded in order to allow appropriate management. Despite similar initial presentations and carrying the same mutation, these brothers had different clinical courses, which emphasizes the phenotypic heterogeneity and inherent genotype-phenotype correlation difficulties of X-linked AHC. Careful monitoring and regular follow-up should be warranted, due to phenotypic characteristics that can appear in later stages and may benefit from therapeutic interventions, such as delayed/precocious puberty. Genetic counseling is essential in order to detect female heterozygotes and offer prenatal testing.